**Question:**

Without actual division, prove that 2x4 – 5x3 + 2x2 – x+ 2 is divisible by x2-3x+2

Thinking Process

(i) firstly, determine the factors of quadratic polynomial by splitting middle term.

(ii) The two different values of zeroes put in biquadratic polynomial.

(iii) In both the case if remainder is zero, then biquadratic polynomial is divisible by

quadratic polynomial.

**Solution:**

Let p(x) = 2x4 – 5x3 + 2x2 – x+ 2 firstly, factorise x2-3x+2.

Now, x2-3x+2 = x2-2x-x+2 [by splitting middle term]

= x(x-2)-1 (x-2)= (x-1)(x-2)

Hence, 0 of x2-3x+2 are land 2.

We have to prove that, 2x4 – 5x3 + 2x2 – x+ 2 is divisible by x2-3x+2 i.e., to prove that p (1) =0 and p(2) =0

Now, p(1) = 2(1)4 – 5(1)3 + 2(1)2 -1 + 2 =2-5+2-1+2=6-6=0

and p(2) = 2(2)4 – 5(2)3 + 2(2)2 – 2 + 2 = 2x16-5x8+2x4+ 0 = 32 – 40 + 8 = 40 – 40 =0

Hence, p(x) is divisible by x2-3x+2.